Pengembangan Bahan Ajar Kreatif untuk Guru MI - Najiah, Najiah (Maliki Interdisciplinary Journal, 2024)
Education in Madrasah Ibtidaiyah (MI) plays a crucial role in shaping students' character and foundational knowledge. However, challenges such as limited resources and a lack of creative teaching materials hinder effective learning. This article discusses the importance of developing innovative teaching materials that enhance student motivation and engagement. The use of diverse methods and technologies in delivering content has proven to create an interactive learning environment. Furthermore, collaboration between teachers and students, along with ongoing assessment, are key elements for an effective learning process. By addressing existing challenges and implementing appropriate strategies, it is hoped that the quality of education in MI can significantly improve, preparing students to face the challenges of the next educational level.